Dampak Risiko Lingkungan Proyek Bandara Dhoho Kediri terhadap Strategi Pemasaran UMKM - Ichwan Setiarso; Widyatmoko Widyatmoko; Choerul Umam (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
Large-scale infrastructure development, such as the Dhoho Kediri Airport project, plays a strategic role in promoting regional economic growth, but it also poses environmental risks that may affect the sustainability of micro, small, and medium enterprises (MSMEs). Changes in the physical and operational environment resulting from construction activities can influence market access, distribution channels, and business location certainty, which in turn affect MSMEs’ marketing strategies. This study aims to analyze the effect of environmental risks arising from the Dhoho Kediri Airport project on the marketing strategies of MSMEs in the affected areas. The research employs a quantitative approach with an explanatory research design and a causal associative method. Data were collected through questionnaires distributed to 76 MSME owners selected using purposive sampling in the sub-districts of Tarokan, Grogol, and Banyakan, Kediri Regency. Data analysis was conducted using multiple linear regression. The results indicate that, partially, environmental pollution, access and distribution disruptions, and business location uncertainty have a positive and significant effect on MSMEs’ marketing strategies. Simultaneously, these environmental risk variables significantly influence marketing strategies, explaining 61.1 percent of the variation in MSMEs’ marketing strategies. The findings suggest that environmental risks from infrastructure projects not only create challenges for MSMEs but also encourage business owners to adapt by adjusting distribution channels, utilizing digital marketing, and redefining market segmentation. The study highlights the importance of local government policy support in the form of marketing assistance, alternative logistics facilitation, and business location certainty to strengthen MSME resilience in areas surrounding strategic infrastructure projects.